2018
DOI: 10.1002/rmb2.12247
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin value and its change prior to methotrexate treatment can predict the prognosis in ectopic tubal pregnancies

Abstract: PurposeTo investigate the role of beta‐human chorionic gonadotropin (HCG) level and its change prior to methotrexate (MTX) treatment as predictors of treatment success and to access the posttreatment observation period for ectopic tubal pregnancy.MethodsClinical data of 41 females treated with MTX for tubal pregnancies were reviewed and analyzed retrospectively.ResultsAmong 41 patients, 34 achieved complete resolution without surgery. No statistically significant difference was observed in the presence of hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In a study conducted by Watanabe et al, 18 ROC analysis showed that prediction of a successful treatment was possible with daily ßHCG changes of <+12.6 with 87% sensivity and 71% specificity and the time interval between the start and the end of treatment was related with first day ßHCG 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Watanabe et al, 18 ROC analysis showed that prediction of a successful treatment was possible with daily ßHCG changes of <+12.6 with 87% sensivity and 71% specificity and the time interval between the start and the end of treatment was related with first day ßHCG 18 …”
Section: Discussionmentioning
confidence: 99%
“…increased the success rate (p < 0.07). 17 In a study conducted by Watanabe et al, 18 ROC analysis showed that prediction of a successful treatment was possible with daily ßHCG changes of <+12.6 with 87% sensivity and 71% specificity and the time interval between the start and the end of treatment was related with first day ßHCG. 18 In Cohen et al's 19 study, the success rate with SD MTX treatment was 75% and the mean changes of ßHCG within 48 h before the start of treatment was significant, moreover a less than 12% increase in ßHCG levels within 48 h before the treatment was a good predictor factor for successful treatment.…”
Section: T a B L Ementioning
confidence: 99%
“…However, in the real world, continuous monitoring of serum hCG cannot be performed for most patients. In a study with a sample size of 41 patients, Watanabe et al found that the treatment success was predicted by % HCG change per day <+12.6% per day 22 . Therefore, we applied the concept of serum hCG daily variation to express the serum hCG trend.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with a sample size of 41 patients, Watanabe et al found that the treatment success was predicted by % HCG change per day <+12.6% per day. 22 Therefore, we applied the concept of serum hCG daily variation to express the serum hCG trend. It was found that MTX success was significantly higher in patients with a daily variation in serum hCG <1.76%/day.…”
Section: Discussionmentioning
confidence: 99%